"Just Pulse it!" Introduction of a conservative implant salvage protocol to manage infection in pre-pectoral breast reconstruction: Case series and literature review. Issue 2 (February 2022) - Marcasciano, Marco; Kaciulyte, Juste; Giuli, Riccardo Di; Marcasciano, Fabio; Torto, Federico Lo; Guerra, Maristella; Prà, Giovanni Dal; Barellini, Leonardo; Mazzocchi, Marco; Casella, Donato; Ribuffo, Diego
Abstract: Post-operative implant infection is generally rare after breast augmentation, but it can occur in up to 35% of cases in post-mastectomy breast reconstruction. Standard treatment consists in the administration of antibiotics, implant removal, and delayed prosthesis replacement leading to multiple operations, with a negative impact on patient's clinical, economical, and psychological outcomes. There is little information published in the literature on the management of periprosthetic infection following pre-pectoral reconstructions. Capsule's removal from a pre-pectoral plane brings the risk of excessive tissue thinning and the compromise of skin flaps viability. In this preliminary multi-center case series, eight patients diagnosed with implant infection following oncological mastectomy and two-stage heterologous pre-pectoral breast reconstruction underwent the same protocol, consisting in tissue expander removal and conservative surgical revision supplemented by an antibiotate pulse lavage of the pocket surface. All patients achieved a successful infection resolution with immediate prosthesis replacement switching the temporary expander to definitive implant. No additional surgical revision was registered during follow-up. The intermittent irrigation is meant to disrupt the biofilm structure and restore antibiotic susceptibility. Moreover, pulse lavage allows the cleansing of the prosthetic capsule, thus avoiding the vascular stress associated with subcutaneous capsulectomy. To the best of our knowledge, this is the first series reporting on the use of Pulsavac in periprosthetic infection following pre-pectoral breast reconstruction, in an attempt to set the basis for an alternative conservative protocol to manage breast implant infection. A thorough literature review on pulse lavage in breast surgery was carried out.